2020
DOI: 10.3390/foods9050675
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and the Subsequent Lockdown Modified Dietary Habits of Almost Half the Population in an Italian Sample

Abstract: The Covid-19 pandemic led to lockdowns in several parts of the world and, hence, changed some daily habits, including social interactions, the ability to perform sports, and—possibly—diet. The Italian government established and promulgated lockdown policies on 9 March 2020. We aim at assessing the effects of Covid-19-induced confinement policies on self-reported food consumption of self-selected Italians by means of a questionnaire that was created and diffused by the Internet. Nearly half, i.e., 49.6% of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

85
580
5
44

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(714 citation statements)
references
References 33 publications
85
580
5
44
Order By: Relevance
“…The number of people who consumed snacks more than 4 times a day increased by 23% in India [ 13 ], while 37.6% of Spaniards [ 18 ] and 30% of Chinese [ 17 ] increased their overall snacking frequency. Instead, the snapshot of Italians and Poles recorded increases in the frequency of consumption by about 60% [ 16 ] and 23% [ 22 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of people who consumed snacks more than 4 times a day increased by 23% in India [ 13 ], while 37.6% of Spaniards [ 18 ] and 30% of Chinese [ 17 ] increased their overall snacking frequency. Instead, the snapshot of Italians and Poles recorded increases in the frequency of consumption by about 60% [ 16 ] and 23% [ 22 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All studies examining the changes in alcoholic beverages consumption concluded that this dropped, except for a Polish survey (showing a 14.6% and 18.1% increase). In detail, 8% of the Indians and 13% [ 14 ] and 36.8% [ 22 ] of the Italians reduced their daily intake by 25–50%. Similarly, the two Spanish surveys reported a 57.3% decrease in the weekly frequency of consumption in the longitudinal observation by Rodríguez-Pérez et al [ 18 ], and a 27% decrease in the cross-sectional evaluation carried out by Romeo-Arroyo et al [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent Italian study, 20% adult patients gained weight and reported an increase in the consumption of "comfort food" (chocolate, ice cream, desserts, salty snacks, etc.) [9]. Rundle et al hypothesized that people, especially children or adolescents, would fare worse concerning weight control at home than when engaged in their usual school curriculum [10].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the obligatory social self-isolation impacts the lifestyle of the population, forcing the adoption of unhealthy dietary habits (increased ultra-processed and re ned foods and decreased fruit and vegetable intake), sedentary behavior, and sleep disturbances. [17] At present, there are no reports in the literature that establish a relation between a change in bowel movement habit and being under the current lockdown. Thus, the aim of our study was to evaluate the incidence of symptoms of constipation and associated factors during the lockdown implemented to contain the spread of COVID-19 in Mexico.…”
Section: Introductionmentioning
confidence: 98%